Problem aspects of doping in modern sports and solutions - Kokoulina, O. P.; Tatarova, S. Y.; Nizametdinova, Z. Kh.; Polishkenea, J. (Theory and Practice of Physical Culture, 2019)
Doping control has long been ranked among the key sport problems faced since the first Olympic Games and still increasingly critical for the global sports on the whole and the national sports in particular. Special medicines in some cases overshadow the traditional daily trainings and competitive progress agendas of some athletes. The study analyzes the potential solutions for the doping control systems based on analyses of the available theoretical and practical literature on the subject and questionnaire surveys of the athletic communities to find solutions for the doping issues. It should be underlined that the modern doping control systems shall be designed with: stringent penalties for the violating coaches and athletes; regular tests; special knowledge and skills advancement trainings for coaches; efficient sport selection systems for gifted children and adolescents; systemic anti-doping campaigns; and upgrades to the doping control systems.